Motivasi Generasi Milenial dalam Beradaptasi dengan Budaya Kerja di PT. X - Dewi Rachmawati; Veronika Trimardhani (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Millennial generation is the generation that lived between 1981 and 1994 ( Howe, N and Strauss, W, 2000). Discussions about this generation are interesting, especially in the world of work. This generation is described as a generation that brings a unique and renewable lifestyle, including the work culture. This study aims to examine how the motivation of the millennial generation in adapting to the work culture at PT. X, one of Badan Usaha Milik Negara (BUMN) in Indonesia. Theories and concepts involved in this research are Motivation and Work Culture. The method used is descriptive qualitative research method with data collection using in-depth interviews with seven main sources and one expert resource who has experience as an human resource practitioner in Badan Usaha Milik Negara (BUMN).The results obtained from this research are that millennial workers are trying to adapt to the work culture in their place of work. The motivation of the millennial generation to work, accordance with Kanfer's theory, they try to fulfill the Direction, Effort & Persistent in their work. Barriers found in adapting to work culture were overcome by leaders communicating top and down and eliminating communication gaps between superiors and subordinates. The value owned by PT. X is implemented to all workers, including the millennial generation. Expert resource interviewed in this study argue that the positive things about the millennial generation working in BUMN is they try to adapt to the work culture in BUMN and this generation also has high achievement oriented at work.